'Catch a falling star': the Winchcombe meteorite fall of 2021. (23rd November 2021) - Simms, Michael J.
Abstract : The fall to the Earth of a meteorite—a piece of rock or metal from Space—is a rare event with fewer than 30 recovered from Britain and Ireland in more than two centuries. Museum curators like myself acquire meteorites mainly through purchases or sample exchange with other museums. Meteorites are so rare that, unlike many rocks and minerals, I cannot reasonably expect to go out and find one, at least not in the UK or Ireland. Or so it seemed until 2021.